Multi-Omics Approach to Evaluate Effects of Dietary Sodium Butyrate on Antioxidant Capacity, Immune Function and Intestinal Microbiota Composition in Adult Ragdoll Cats - Anxuan Zhang; Deping Li; Tong Yu; Mingrui Zhang; Yingyue Cui; Haotian Wang; Tianyu Dong; Yi Wu (Metabolites)
Objectives: Sodium butyrate (SB) is a typical postbiotic known to positively affect economic animals in recent years, but research on SB in pet cats is scarce. Consequently, this study sought to explore the influence of SB on anti-inflammatory and antioxidant capacity, immune function, and gut microbiota of adult cats through the assessment of biochemical parameters and comprehensive integrative omics analysis. Methods: A total of 30 adult cats were divided into three groups: a basal diet (NC), basal diet with 0.05% SB (SB5), and basal diet with 0.1% SB (SB10). The experiment lasted for 6 weeks. Results: The results indicated that the fecal level of calprotectin was lower in the SB10 group than in the SB5 and NC groups. The SB10 group reduced the serum levels of TNF-α, IL-1β and DAO compared with the NC group (p < 0.05). In addition, the SB10 diet increased the GSH-Px level and decreased MDA content compared with the NC diet (p < 0.05). Transcriptomic analysis showed that the gene expression of VCAM1 exhibited a notable decrease in the SB10 group compared to the NC group (p < 0.05). The analysis of gut microbiota revealed that the richness of gut microbiota was higher in the SB10 than in the NC group (p < 0.05), and the abundance of Lachnospiraceae, Lachnoclostridium, Blautia, and Roseburia was greater in the SB10 than in the NC group (p < 0.05). Conclusions: Dietary SB could enhance the antioxidant and anti-inflammatory capacity, improve immune function, and positively regulate the gut microbiota composition in adult cats.